NEW DEEP-SEA BRYOZOAN SPECIES FROM THE PLEISTOCENE OF SOUTHERN ITALY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1998)
Two new species: Tervia barrieri (Cyclostomatida) and Heliodoma angusta (Cheilostomatida) together with the subspecies Crisia tenella Calvet longinodata (Cyclostomatida) are described from Pleistocene deep-sea sediments cropping out in Southern Italy. They are Mediterranean palaeoendemics, closely related to Recent deep-water Atlantic species.